К вопросу о содержании некоторых лингвистических терминов, Вестник ЦМО МГУ. Филология. Культурология. Педагогика. Методика. 2010. № 1. Стр. 28-31 – М: ЦМО МГУ 2010. On the Issue of the Meaning of some Linguistic Terms. In: Journal of the Centre of International Education, Moscow State University. Philology. Culturology. Pedagogy. Methodology. Moscow, Russia, pp. 28-31. ISSN 2074-8361 - Csajbok-Twerefou, I. (My University, 2010)
В статье рассматриваются некоторые термины, употребляемые в русской и венгер-ской лингвистической науке для обозначения слов иностранного происхождения. Исследование показывает, что употребление этих терминов не однозначно и зависит от степени освоения языком данного слова. Ключевые слова: заимствования, проникновения, слова-пришельцы, иностранные слова, освоение, термины. The paper discusses the use of terminologies in representing “borrowings” and “loanwords” in Russian and Hungarian languages. Analysis indicates that in Russian, terminologies used for borrowed words are not monosemantic. In Hungarian, though the terminologies used are not monosemantic their use is less complex. Terminology used for a specific borrowed word depends on how useful the word is in Russian or Hungarian and the stage of its adoption.
Keywords: borrowed words; loanwords; foreign words; adoption; terminology